A Stylistic Study Of Arabic Poem By Hashem Salih Manna/ دراسة أسلوبية لقصيدة لهاشم صالح مناع - Aldhafeeri, Thana Hussain (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
The importance of the research lies in the fact that it deals with a poem by a contemporary poet, which is a poem (On Spinning and Complaining) by Hashem Salih Manna, and studies it stylistically. phonetic, semantic, synthetic, and rhetorical), and this research relies on the stylistic approach, which is based on the analysis of literary texts and the interpretation of the relationship between their parts, their purpose, and the statement of their aesthetics. The researcher reached a set of results, the most important of which are: stylistics is a science concerned with the study of the literary text in form and content based on analysis and interpretation, showing its aesthetics, and the abundance of stylistic characteristics in the poem (On Spinning and Complaining) by Hashim Manna; The reason for this is that the poet organized his poem to be an application of stylistic studies, and the poet diversified the semantic fields, and used simple and accurate language and appropriate words for the situation he spoke about in a wonderful and elegant manner.